Study on Mechanism of Scalp Electro-acupuncture in Treating Ischemic Stroke Based on CT Localization - 牛文民 李忠仁 (Journal of acupuncture and tuina science, 2006)
Objective: To investigate an effective method of treating ischemic stroke.Methods: The scalp area corresponding to the ischemic focus was electro-acupunctured by craniocerebral CT localization. Cerebral blood flow and blood rheology were measured.Results: The curative effect and changes in cerebral blood flow and hemorheologic indices were better in the observation group than in the control group (P<0.05).Conclusion: Scalp electro-acupuncture based on CT localization is an effective method of treating ischemic stroke.